ISOLASI DAN IDENTIFIKASI BAKTERI PENYEBAB BUSUK LUNAK PADA UMBI WORTEL (Daucus carota L.) VARIETAS LOKAL DI BALI - Ni Wayan Desi Bintari; Retno Kawuri; Meitini Wahyuni Proborini (Metamorfosa: Journal of Biological Sciences, 2015)
Soft rot bacteria infection in carrot tuber (D. carota L.) causes severe economic losses. Soft rot disease can be caused by various bacteria belonging to Enterobacteriaceae. This study aimed to isolate and identify bacteria as causal agent of soft rot disease in local carrot variety in Bali. Samples were collected at Badung Tradisional Market, Denpasar, Bali. Isolation was carried out by serial dilution method (Platting Method). Eight bacteria (BL1, BL2, BL3, BL4, BL5, BL6, BL7 and BL8) were isolated from soft rot tuber. BL6 isolate showed positive result in Postulat Koch test that caused soft rot on carrot tuber. The result of identification by Microgen™ GnA+B-ID System and identification book Bergeys’s Manual of Determinative Bacteriology Ninth Edition (Holt et al., 1994), BL6 was identified as Citrobacter.